PERAMPASAN BARANG BUKTI NARKOTIKA (Studi Penerapan Pasal 101 ayat (1) Undang-Undang Nomor 35 tahun 2009 tentang Narkotika di Pengadilan Negeri Purbalingga) - Bagus Trenggono (Jurnal Idea Hukum, 2017)
Evidence of narcotics is forbidden and the goods that are harmful, deprivation of evidence of narcotics within the provisions of Article 101 paragraph (1) of Law No. 35 of 2009 on Narcotics is the thing that is right. Reason or rationale for the seizure of narcotics evidence to the State have legitimate reasons or technical reasons or practical. For legitimate reasons set forth in the provisions of Article 101 paragraph (1) of Law No. 35 of 2009 on Narcotics whereas technical or practical reasons provide facilities for research institutions and the pharmaceutical industry to obtain narcotics. Decisions of Judges Purbalingga stating evidence of narcotics seized for the State and for subsequently destroyed are not contrary to the provisions of Article 46 paragraph (2) Criminal Procedure Code as the legal aspects of the show in culling evidence of narcotics and as a legal ground in doing appropriation evidence of narcotics had in accordance with the provisions in Article 10 letter b of the Criminal Code and Article 39 paragraph (1) of the Criminal Code.Â Key words : Decisions of Judges, extermination, Narcotics, plunder